K-Pop Marketing Tactics That Build Fanatical Behavior - Andri Ardhiyansyah; Dwi Putri Maharani; Sintia Permata Sari; Umar Mansur (Nusantara Science and Technology Proceedings, 2020)
Kpop fans are known for their loyalty, they support their idols by buying albums, streaming music videos (MV), following concerts, fan meetings, fanservice, and many more. K-Pop fans are synonymous with fanaticism where K-pop fans are never separated from goods or merchandise related to their idols such as albums, lightsticks, photo cards, and other merchandise or by coming to every fan meeting, fan sign, Showcase, and idol concert. K-Pop fans are always considered excessive and always consumptive, and fan fanaticism is shown by joining the K-Pop fan community as their existence in providing information about K-Pop idols. This study aims to collect and analyze articles related to K-Pop marketing that causes fanaticism towards K-pop fans. The design used is a literature review, a critical analysis of the research being carried out on a specific topic of a scientific section. articles are collected using search engines such as Scopus and Google Scholar. Based on the articles collected, it is found that an interesting album and a concert that makes a happy experience can build a sense of love that leads to fanatical behavior. The album marketing strategy carried out by the South Korean entertainment agency makes K-Pop fans consume which is not only driven by efforts to meet their needs, but they have a sense of satisfaction from buying the K-Pop album